Comparative Analysis of Resource Utilization on 2.4 GHz and 5.8 GHz Wireless LAN Network Frequencies (OpenWrt Firmware Case Study) - Santosa, Ria; Haq, Abdul; Khanif, M. (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2024)
The purpose of this study is to analyze the comparison of the use of dual-band wireless router device resources on the 2.4 GHz 802.11n standard network and 5.8 GHz 802.11ac standard using a 40 MHz frequency using the Linksys EA7500 version 2 router with OpenWrt firmware case study with supporting IPerf3 and HTop applications. The research results obtained in the study compare throughput and resource usage using wireless LAN networks at frequencies of 2.4 GHz and 5.8 GHz. The use of 5.8 GHz frequency in the same frequency (40MHz) range results in higher throughput, which has practical implications for network engineers and researchers. While using CPU and RAM at a frequency of 2.4 GHz, it is concluded that every 1% utilization of the CPU can transfer data at 0.78 Mbit/sec, or 6.24 MBps, and for a frequency of 5.8 GHz, it is 1.11 Mbit/sec, or 8.88 MBps. While in the use of RAM, it is concluded that every 1% of RAM can be used to transfer data 0.32 Mbit/sec or 2.56 MBps for frequency 2.4 GHz and frequency 5.8 GHz, which is 1.32 Mbit/sec or 10.56 MBps.